To find the value of x, we need to first simplify the expression inside the parenthesis:
4 - 1 = 3
Now we have:
15/22 - 3 + 5/6
Now, we need to convert 3 into a fraction with the same denominator as 22 and 6:
3 = 3*(6/6) = 18/6
Now the expression becomes:
15/22 - 18/6 + 5/6
To combine these fractions, we need to have a common denominator, which is 22*6=132.
So, we need to rewrite the fractions with a denominator of 132:
15/22 6/6 = 90/13218/6 22/22 = 396/1325/6 * 22/22 = 110/132
Now, the expression becomes:
90/132 - 396/132 + 110/132 = -196/132
Now the expression is equal to -196/132, which simplifies to -49/33.
Therefore, x = -49/33.
To find the value of x, we need to first simplify the expression inside the parenthesis:
4 - 1 = 3
Now we have:
15/22 - 3 + 5/6
Now, we need to convert 3 into a fraction with the same denominator as 22 and 6:
3 = 3*(6/6) = 18/6
Now the expression becomes:
15/22 - 18/6 + 5/6
To combine these fractions, we need to have a common denominator, which is 22*6=132.
So, we need to rewrite the fractions with a denominator of 132:
15/22 6/6 = 90/132
18/6 22/22 = 396/132
5/6 * 22/22 = 110/132
Now, the expression becomes:
90/132 - 396/132 + 110/132 = -196/132
Now the expression is equal to -196/132, which simplifies to -49/33.
Therefore, x = -49/33.